A new genus of leaf litter inhabiting Neotropical Monoplatina (Coleoptera: Chrysomelidae: Galerucinae: Alticini) - Linzmeier, Adelita M.; Konstantinov, Alexander S. (Zootaxa, 2012)
A new genus (Andersonaltica) containing five new species (A. denticulata, A. elongata, A. pecki—the type species of thegenus, A. tuberosa, and A. valens) from Central America is described and illustrated. It is compared to Aedmon Clark,Apleuraltica Bechyne, Distigmoptera Blake, Hypolampsis Clark, and Pseudolampsis Horn and a key to identification of these genera is provided.